(untitled) (Journal of Contemporary Philology, 2021)
In this text we refer to slam poetry, as a performing way of presenting literature. Slam poetry is most often performed at Poetry slam competitions, festivals and other events. It is a product of urbanity and urban lifestyle and is influenced by hip hop music. The mixture of slam poetry with hip hop and other forms of expression, especially among the younger population, contributes to changing or improving the attitude towards poetry and the performing arts. Slam poetry points out problems and problematizes certain already existing and generally accepted attitudes, conditions, and critically addresses the undesirable tendencies in the society. The techniques of making slam that are considered relevant refer to the structure, language and meaning of slam poetry. Slam functions through a language which has its own terminology and has its own poetics. Structurally, the verses can be rhymed or free, organized in stanzas, with or without punctuation. Special attention is paid to the melody and rhythm that the skilled performer uses to stress and emphasize the verses that they consider important for their performance. With its lively and playful interpretation, free from the classical notions of poetry as a genre, slam poetry and Poetry slam manifestations inspire new generations of poets who are enabled to share their views with a wider audience.